2018
DOI: 10.1002/ijc.31661
|View full text |Cite
|
Sign up to set email alerts
|

Expression of LAG‐3 and efficacy of combination treatment with anti‐LAG‐3 and anti‐PD‐1 monoclonal antibodies in glioblastoma

Abstract: Like in many tumor types, immunotherapy is currently under investigation to assess its potential efficacy in glioblastoma patients. Trials are under way to assess the efficacy of new immune checkpoint inhibitors including anti‐PD‐1 or CTLA4. We here investigate the expression and efficacy of a novel immune‐checkpoint inhibitor, called LAG‐3. We show that LAG‐3 is expressed in human glioblastoma samples and in a mouse glioblastoma model we show that knock out or LAG‐3 inhibition with a blocking antibody is effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 19 publications
2
101
0
1
Order By: Relevance
“…These successes have led to the exploration of additional inhibitory signaling pathways on immune cells. LAG-3 receptor is another inhibitory checkpoint on T cells; its potential role in cancer is supported by extensive preclinical studies (8,22,23). Notably, analysis of mouse and human tumors suggests that coexpression of LAG-3 and PD-1 is associated with T-cell dysfunction (21,22), indicating that inducible LAG-3 expression on activated T cells could be a potential mechanism of therapeutic resistance to PD-1 checkpoint blockade (46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These successes have led to the exploration of additional inhibitory signaling pathways on immune cells. LAG-3 receptor is another inhibitory checkpoint on T cells; its potential role in cancer is supported by extensive preclinical studies (8,22,23). Notably, analysis of mouse and human tumors suggests that coexpression of LAG-3 and PD-1 is associated with T-cell dysfunction (21,22), indicating that inducible LAG-3 expression on activated T cells could be a potential mechanism of therapeutic resistance to PD-1 checkpoint blockade (46).…”
Section: Discussionmentioning
confidence: 99%
“…CD8 þ T cells coexpressing PD-1 and LAG-3 display severely impaired effector functions in a murine model of self-antigen tolerance (21), and antigen-specific T cells in human ovarian cancer are negatively regulated by PD-1 and LAG-3 (20). Multiple reports demonstrate that a large fraction of PD-1-expressing CD8 þ and CD4 þ tumor-infiltrating lymphocytes (TIL) coexpress LAG-3, supporting the dominance of PD-1 in modulating antitumor T-cell responses, as well as a direct role of LAG-3 in further suppressing the activity of a subset of PD-1expressing T cells (18,(20)(21)(22)(23)(24). Mice deficient for both PD-1 and LAG-3 show spontaneous autoimmunity and lethality, not seen in either single knockout (22,25).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…is regulated by inhibitory and active receptors, remarkably impact cancer immune escape [33] . Research indicated that TILs would get activated if PD-1 or LAG-3 pathway alone was blocked, either by antibodies or knocking down [34] . From a mechanistic standpoint, LAG-3 blockade is equal to the blockade of the binding between LAG-3 and HLA-II molecules.…”
Section: Cox Regression Analysis Of Rfsmentioning
confidence: 99%
“…LAG-3 has remarkable synergy with PD-1, disrupting immune responses to cancer cells [37] . According to existed research, compared with blocking either LAG-3 or PD-1 alone, blocking both pathways showed much more remarkable therapeutic e cacy for cancers [30,34] . Another study reported upregulated expression of LAG-3 in patients insensitive to PD-1 blocking treatment, thus combined strategy will improve the prognosis [29,36] .…”
Section: Cox Regression Analysis Of Rfsmentioning
confidence: 99%